2021
DOI: 10.3390/v13060960
|View full text |Cite
|
Sign up to set email alerts
|

Anti-SARS-CoV-2 Activity of Surgical Masks Infused with Quaternary Ammonium Salts

Abstract: The SARS-CoV-2 pandemic has highlighted the need for protective and effective personal protective equipment (PPE). Research has shown that SARS-CoV-2 can survive on personal protective equipment, such as commonly used surgical masks. Methods are needed to inactivate virus on contaminated material. We show here that embedding viral-disinfecting compounds during the manufacturing of surgical masks inactivates a high dose (up to 1 × 105 pfu) of live, authentic SARS-CoV-2 within minutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In this regard, natural anti-SARS-CoV-2 products could limit the concerns about in vivo usage, which remain to be thoroughly studied in all such surface inhibitory applications. Selwyn and colleagues [ 33 ] showed SARS-CoV-2 inactivation after 5, 20, and 60 min using a combination of a natural citric acid with 3% thymol and 1297 quaternary ammonium compound which was infused in surgical masks.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, natural anti-SARS-CoV-2 products could limit the concerns about in vivo usage, which remain to be thoroughly studied in all such surface inhibitory applications. Selwyn and colleagues [ 33 ] showed SARS-CoV-2 inactivation after 5, 20, and 60 min using a combination of a natural citric acid with 3% thymol and 1297 quaternary ammonium compound which was infused in surgical masks.…”
Section: Resultsmentioning
confidence: 99%
“…[ 12 ] On the other hand, Selwyn et al manufactured a surgical mask infused with QAS to inactivate SARS‐CoV‐2 in a rapid and safe manner. [ 13 ] Also, Ikner et al proposed and evaluated a QAS polymer coating against SARS‐CoV‐2. [ 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Quaternary ammonium salts (QAS) represent an accessible antiseptic with antiviral properties that could be used against SARS-CoV-2 due to their ability to form active bonds capable of breaking the protein capsid of different viruses and bacteria. [9][10][11][12][13][14] Ogilvie et al formulated different quaternary ammonium disinfectants, demonstrating that their formulations rapidly inactivate SARS-CoV-2, making them potentially useful for controlling SARS-CoV-2 spread in hospitals and the community. [12] On the other hand, Selwyn et al manufactured a surgical mask infused with QAS to inactivate SARS-CoV-2 in a rapid and safe manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that BACs could effectively inactivate 99% of SARS-CoV-2 particles in one minute of contact and methicillin-resistant Staphylococcus aureus and Staphylococcus epidermis ( Martí et al, 2021 , Tuñón-Molina et al, 2021 ), indicating their possible preventive use among healthcare workers and researchers. Surgical masks infused with QACs were also reported to inactivate a high dose of up to 1 × 10 5 pfu (plaque-forming units) of live SARS-CoV-2 within minutes ( Selwyn et al, 2021 ).…”
Section: Classification Mechanism Of Action and Applications Of Qacsmentioning
confidence: 99%